2006
DOI: 10.1074/jbc.m605938200
|View full text |Cite
|
Sign up to set email alerts
|

HCF164 Receives Reducing Equivalents from Stromal Thioredoxin across the Thylakoid Membrane and Mediates Reduction of Target Proteins in the Thylakoid Lumen

Abstract: HCF164 is a membrane-anchored thioredoxin-like protein known to be indispensable for assembly of cytochrome b 6 f in the thylakoid membranes. In this study, we report the finding that chloroplast stroma m-type thioredoxin is the source of reducing equivalents for reduction of HCF164 in the thylakoid lumen, providing strong evidence that higher plant chloroplasts possess a trans-membrane reducing equivalent transfer system similar to that found in bacteria. To probe the function of HCF164 in the lumen, a screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 63 publications
5
145
0
Order By: Relevance
“…Recently, Motohashi and Hisabori (2006) reported that several thylakoid membrane proteins interact with HCF167, a thioredoxinlike protein in thylakoids. All of the proteins they identified, including cytochrome f, Rieske FeS protein, PSI-N, LHCB5, FTSH2, FTSH8, and three CF 1 subunits of ATPase, have multiple Cys residues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Motohashi and Hisabori (2006) reported that several thylakoid membrane proteins interact with HCF167, a thioredoxinlike protein in thylakoids. All of the proteins they identified, including cytochrome f, Rieske FeS protein, PSI-N, LHCB5, FTSH2, FTSH8, and three CF 1 subunits of ATPase, have multiple Cys residues.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the topology of CYO1 in the thylakoid membrane, we performed a protease protection assay (Motohashi and Hisabori, 2006). Incubation of sonicated thylakoid membrane samples with the protease thermolysin resulted in the degradation of FNR, which is located on the stroma-exposed surface of thylakoid membranes, and PSI-N (for the N subunit of photosystem I), which is located on the lumen-exposed surface of the thylakoid membrane.…”
Section: Subcellular Localization Of Cyo1mentioning
confidence: 99%
See 1 more Smart Citation
“…Other Proteins-Recombinant thioredoxin-f of S. oleracea was expressed in E. coli and purified as described (23). Chloroplast F 1 -ATPase (␣ 3 ␤ 3 ␥␦⑀) was purified from fresh market spinach leaves (24) and the ␦ and ⑀ subunits were removed by the following procedures.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about Trx-regulation in the lumen. It is only recently that a Trx-like protein was found within the lumen, leading to a new field of exploration [7]. In that study, it was shown that the protein HCF164 can reduce Cys residues of the PSI subunit PsaN.…”
Section: Introductionmentioning
confidence: 99%